Toxicity Assessment of Titanium Dioxide Nanoparticles in E. coli Mutant with Truncated Lipopolysaccharide (LPS) - Sharma, Poonam (Trends in Sciences, 2022)
As the production and use of titanium dioxide nanoparticles (TiO2NPs) have increased, so has concern over their environmental impact. Bacteria play an important role in ecological processes and may be harmed by these nanoparticles’ toxicity. The specific mechanisms of TiO2NPs toxicity towards bacteria, as well as the primary role of bacterial cell surface composition, are so far not fully recognized. The impact of TiO2NPs exposure on both wild strain, E. coli K 12 W3110, and LPS biosynthesis pathway galU gene mutant was assessed in the present study to gain insight into the underlying mechanisms contributing to TiO2NPs toxicity. We demonstrate that a truncated LPS causes increased sensitivity to TiO2NPs. During the experiment, TiO2NPs formed aggregates with bacteria, and the electrophoretic mobility test revealed a higher interaction between nanoparticles and bacteria due to the positive and negative charge on their surfaces. The high sensitivity of the galU mutant to TiO2NPs may be attributed to the shorter LPS and also possibly with outer membrane efflux proteins like TolC and porins/OmpF, which provide stability to the outer membrane while also acting as permeability barriers to hazardous substances like chemicals, detergents, antibiotics and nanoparticles. HIGHLIGHTS The present study highlights the role of the morphological features of bacteria involved in TiO2NPs toxicity at the molecular level LPS in the bacteria act as an efficient barrier function as truncated LPS makes the bacteria more sensitive to TiO2NPs The changed expression of TolC efflux proteins and OmpF/C porin proteins due to galU mutation can possibly lead to disturbed cell signaling and instability of the outer membrane GRAPHICAL ABSTRACT